On Ingram’s Conjecture - Block, Louis; Jakimovik, Slagjana; Keesling, James (Department of Mathematics & Statistics Auburn University, Alabama 36849, USA, 2006)
In this paper, we consider inverse limit spaces (I, fs) where the bonding map fs is a tent map with s ∈ (√2, 2]. We make a conjecture concerning homeomorphisms of (I, fs). We show that if our conjecture is true, then Ingram’s conjecture holds.
Keywords: composant, continuum, Ingram’s conjecture, inverse limit space, pseudo-isotopy, tent family